EFFECT OF SLAUGHTERING TECHNIQUES ON THE QUALITY OF FRESH “PATIN SIAM “ CATFISH (Pangasius hypopthalmus) STORED AT AMBIENT TEMPERATURE - Diah Ikasari; Theresia Dwi Suryaningrum (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
Fish handling is one of factors that affect fish quality deterioration, including slaughtering technique. In this study, the quality deterioration of fresh patin Siam catfish (Pangasius hypopthalmus) which were handled with different slaughtering techniques was observed. Fish were fasted for one day before slaughtered with two different techniques namely live-chilling and bleeding techniques. Live-chilling technique was conducted by exposing  fish into cold water with temperature of 0-5°C for 15 minutes, while bleeding technique was conducted by cutting directly on the arteries part of fish head. After being slaughtered, fish were then stored at ambient temperatures for 18 hours and observed for its quality deterioration in every 3 hours. The observed parameters of fish quality deterioration were including the sensory attributes which were described using descriptive test by trained panelists; chemical parameters including proximate analysis; pH and Total Volatile Base (TVB), and microbiological parameters including Total Plate Count (TPC), coliform and E.coli. Results showed that the flesh of patin Siam catfish slaughtered by live-chilling technique had more blood in the fish body tissue, while bleeding technique resulted in much brighter flesh as well as abdominal cavity. The flesh quality decreased after 18 hours of storage in both treatments, but no significant changes in their proximate values. Bleeding technique was more recommended compared to live-chilling technique for slaughtering patin Siam catfish due to its predominance in producing better flesh quality.